2013
DOI: 10.1080/10408398.2011.582544
|View full text |Cite
|
Sign up to set email alerts
|

Cyclodextrins and Antioxidants

Abstract: In recent years, the growth of the functional foods industry has increased research into new compounds with high added value for use in the fortification of traditional products. One of the most promising functional food groups is those enriched in antioxidant compounds of a lipophilic nature. In spite of the numerous advantages reported for such antioxidant molecules, they may also have disadvantages that impede their use in functional foods, although these problems may well avoided by the use of encapsulant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
52
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(58 citation statements)
references
References 140 publications
3
52
0
3
Order By: Relevance
“…In Ram particularly, cyclodextrins-cholesterol complex has been reported to improve motility, viability and membrane integrity (Ahmad et al, 2013;Awad, 2011;Mocé et al, 2010;Motamedi-Mojdehi et al, 2014). Cyclodextrins are oligosaccharides with an internal hydrophobic cavity which forms inclusion complexes with various hydrophobic guest molecules, including cholesterol and lipophilic vitamins, and an external hydrophilic face increasing their solubility in semen extenders (Dodziuk, 2006;López-Nicolás et al, 2012).…”
Section: Introductionmentioning
confidence: 97%
“…In Ram particularly, cyclodextrins-cholesterol complex has been reported to improve motility, viability and membrane integrity (Ahmad et al, 2013;Awad, 2011;Mocé et al, 2010;Motamedi-Mojdehi et al, 2014). Cyclodextrins are oligosaccharides with an internal hydrophobic cavity which forms inclusion complexes with various hydrophobic guest molecules, including cholesterol and lipophilic vitamins, and an external hydrophilic face increasing their solubility in semen extenders (Dodziuk, 2006;López-Nicolás et al, 2012).…”
Section: Introductionmentioning
confidence: 97%
“…Another important feature of the inclusion complexes is a dynamic equilibrium between the free molecules and the complex in solution, which is characterized by a stability constant K. The ability of cyclodextrins to form inclusion complexes has propelled their use as molecular containers to increase not only the water solubility of highly hydrophobic molecules but also their stability and bioavailability (Passos et al, 2012). This is reflected by their widespread utilization in pharmaceutical, food, chemical and other industrial areas to encapsulate colors, flavors, fatty acids or vitamins (Davis & Brewster, 2004;López-Nicolás, Rodríguez-Bonilla, & García-Carmona, 2014;Szente & Szejtli, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…The majority of these publications demonstrated improved the water solubility, stability, and bioavailability of different polyphenols due to inclusion complex formation. In general, CD derivatives such as HPβCD were more efficient as complexation agents compared to parent βCD and, in many cases, an increased antioxidant capacity of CD encapsulated polyphenols was observed [16,17]. Taking all of this into account, it seems that the use of CD aqueous solutions as an extraction medium could be a valid approach to efficiently extract bioactive compounds from the plant material, especially taking into account the results of Yatsu et al [18], who demonstrated the possibility of the simultaneous complexation of daidzein, genistein, and glycitein from an enriched soy fraction with the HPβCD.…”
mentioning
confidence: 99%
“…Zhang et al [27] have demonstrated that the stability constant of the inclusion complex of caffeic acid with HPβCD is 112 M −1 , while for flavonols such as myricetin, quercetin, and kaempferol, the stability constants are in the range of 5494-12 456 M −1 [28], clearly demonstrating their high efficiency for inclusion complexation. On the other hand, the complex structure of tannins would impair their interaction with HPβCD by steric reasons [17]. The most important outcome of the inclusion complex formation is in the solubility increase of the included molecule [15].…”
mentioning
confidence: 99%